PEMANFAATAN INFORMATION AND COMMUNICATIONS TECHNOLOGY (ICT) SEBAGAI SUMBER BELAJAR DI ERA DIGITAL - Haryati Haryati; Yolin Erwin (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is library research, it is intended that the principle in conducting research utilizes data sources that have been available in various forms of writing. The purpose of this study is to illustrate that ICT can be used as a very relevant learning resource in the digital age today. The research method used is a qualitative research method with a type of literature study. The data used is secondary data. The results obtained from the research conducted that ICT has many impacts in the development of the learning process. The impact generated by ICT is not only positive, but also has a negative impact. However, in this study, one of the positive impacts of ICT was to be a source of learning in the digital era. The use of ICT in learning can optimize the statement that lifelong learning through distance education, asynchronous mode learning in which participants learn or communicate independently at different times anytime they are online (anytime-anywhere learning), and close professional isolation space during this is often felt in learning. The products resulting from ICT that can be used as learning resources are e-learning, e-books, e-libraries, e-modules, online tutorials, educational television, educational radio, interactive multimedia and virtual laboratories. So it was concluded that ICT can be used as a source of learning in the digital era.